The Ward Method of music instruction and its reception in Spain. Between the Social Question and Motu Proprio (Ca. 1873-1965) - Ramón Salinas, Jorge; Zavala Arnal, Carmen M. (Historia y Memoria de la Educación, 2022)
This article reflects on the meaning and scope of the Ward teaching method, which was conceived at the time in a general way for developing musical literacy in schoolchildren as well as providing a basic musical learning of Gregorian Chant. We also delve into the figure of its creator, the American pedagogue Justine Bayard Cutting Ward (1879-1975), paying special attention to the conjuncture and contextualization of the time in which her musical system developed. Subsequently, the issue of the reception of the Ward method in Spain is addressed, framed by the crisis affecting the Church in the nineteenth century, the Social Question addressed by Pope Leo XIII and the subsequent reform of Sacred Music championed by Pius X and ratified until the Second Vatican Council (1962-1965). This method of musical teaching also takes as a reference the revitalization and normalization of the Gregorian chant from Solesmes. The review that is proposed here through the analysis of the origin of the Ward method as well as the combination of factors and circumstances that led to it may contribute to updating some of its premises in the pedagogical-musical field, whose basic principles are still a valid influence on some of the main methods employed in music education.